2022
DOI: 10.1371/journal.pone.0262545
|View full text |Cite
|
Sign up to set email alerts
|

Molecular perturbations in pulmonary tuberculosis patients identified by pathway-level analysis of plasma metabolic features

Abstract: Insight into the metabolic biosignature of tuberculosis (TB) may inform clinical care, reduce adverse effects, and facilitate metabolism-informed therapeutic development. However, studies often yield inconsistent findings regarding the metabolic profiles of TB. Herein, we conducted an untargeted metabolomics study using plasma from 63 Korean TB patients and 50 controls. Metabolic features were integrated with the data of another cohort from China (35 TB patients and 35 controls) for a global functional meta-an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Notably, our previous work consistently highlighted the role of lipids in the pathogenesis of TB and their potential to aid in TB management [21,42]. We also found that host metabolic perturbations in TB were associated with innate immune responses to the pathogen [22]. PC has been implicated in the host immune response to pathogens [21,42,43], and PC-derived lipid mediators play a role in immune modulation [44].…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Notably, our previous work consistently highlighted the role of lipids in the pathogenesis of TB and their potential to aid in TB management [21,42]. We also found that host metabolic perturbations in TB were associated with innate immune responses to the pathogen [22]. PC has been implicated in the host immune response to pathogens [21,42,43], and PC-derived lipid mediators play a role in immune modulation [44].…”
Section: Discussionmentioning
confidence: 62%
“…A universal diagnostic test capable of differentiating TB from NTM, other lung diseases, LTBI, and healthy individuals remains necessary [14]. Circulating immune and metabolic biomarkers hold promise for this purpose [19][20][21][22][23]. For example, Hur et al identified several cytokines, such as interleukin-2, as potential adjunctive biomarkers for distinguishing TB from NTM [19].…”
Section: Introductionmentioning
confidence: 99%
“…Horizontal (metabolomics and lipidomics) and vertical (genomics, transcriptomics, proteomics, and metabolomics) multi-omics data integration present a powerful approach to capture a holistic view of the molecular landscape, which could provide a comprehensive understanding of an individual's response to anti-TB drugs [ 123 , 124 ]. These approaches are described as prospects to improve the better-personalized medicine of TB and allow the discovery of biosignatures for treatment monitoring and clinical outcomes (efficacy and AEs) [ 123 , [125] , [126] , [127] ]. Long et al.…”
Section: Six Primary Prospects In Tb Clinical Managementmentioning
confidence: 99%